Analysis of Distribution Patterns of Environmental Risk Factors with Malaria Incidents in the Working Area of the Tanjung Tiram Community Health Center, Batu Bara Regency - Nurmala Hayati Sihombing; Theodorus Teddy Bambang Soedjadi; Deli Syaputri; Samuel Marganda Halomoan Manalu; Desy Ari Apsari (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Environmental conditions have a big influence on the incidence of malaria because a bad environment can increase the breeding and proliferation of Anopheles mosquitoes. The aim of this research is to determine environmental risk factors and distribution patterns of malaria in the Tanjung Tiram Community Health Center working area, Batubara Regency. This research method is analytical observational with a case control research design and an ecological approach. This research was conducted in the working area of the Tanjung Tiram Health Center, Batu Bara Regency, which was carried out from April to July 2023. Population 40,604 people. The sampling technique was purposive sampling so that the research sample was 100 people. Data collection uses questionnaires and observation sheets. Data analysis using the bivariate Chi square test on SPSS version 20 software and Analysis of malaria case distribution mapping using the Geographic Information System (GIS) application to describe the distribution pattern of malaria in Batubara Regency. The results of the study show that there is a relationship between environmental risk factors such as ceilings (p-value=0.000), wall type (p-value=0.000), ventilation (p-value=0.000), wall density (p-value=0.000), partitions on windows (p-value=0.000), the presence of puddles (p-value=0.000), gutters (p-value=0.000) and swamps around the house (p-value=0.000). The distribution of Malaria cases in Tanjung Tiram District, Batubara Regency is not spread across all areas in the district, this means that the highest number of malaria cases occur in mixed plantation areas. By depicting the distribution pattern in the form of a map, it can optimize the reduction in the incidence of malaria cases. Keywords: Environment, Geographic Information System, Malaria